Application of fern Davallia denticuluta L. extract using different solvents as biostimulants for Kopay chili (Capsicum annuum L.) production - Suwirmen; Zozy Aneloi Noli; Fepi Dwi Marta; Chairul (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Ferns are a potential source of biostimulant compounds due to their rich content of bioactive secondary metabolites. This study aimed to evaluate different solvents for extracting bioactive compounds from Davallia denticulata and to identify the optimal extract formulation for enhancing the growth and yield of Kopay chili. This research was conducted from February to May 2024 at the Plant Physiology Research Laboratory and Greenhouse, Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Andalas, Padang. A completely randomized design with 16 treatment combinations involving four solvents (A1 = aquadest, A2 = methanol, A3 = ethanol, A4 = butanol) and four extract concentrations (B0 = 0 mg L-1, B1 = 25 mg L-1, B2 = 50 mg L-1, and B3 = 100 mg L-1) was employed. Plant growth parameters responded differently to various combinations of extract concentration and solvent type. Methanol extract at 100 mg L-1 significantly increased plant height, ethanol at 50 mg L-1 improved shoot dry weight and root biomass, butanol at 100 mg L-1 increased chlorophyll b and total chlorophyll, and methanol at 25 mg L-1 resulted in higher fruit weight. These results indicate that Davallia denticulata extract, when properly formulated, holds strong potential as a natural biostimulant to improve growth and productivity in chili cultivation. Keywords: active compouns; chili growth; plant extract; secondary metabolites; solvents extraction